Integrating computational thinking in children aged 3 to 6: challenges and opportunities in early childhood education - Perez Valdes, Gineth Paola; Boude Figueredo, Oscar; Vargas Sanchez, Ana Dolores (Frontiers in Education, 2025)
Computational thinking (CT) has emerged as a crucial skill in 21st-century education. Although most research has focused on education levels beyond primary school, this article reviews the impact of its integration in early childhood education, specifically for children aged 3–6 years old. Through a systematic review of 84 studies published in Scopus and Web of Science between 2013 and 2023, pedagogical strategies and technological tools used to develop CT in early childhood are explored. The findings reveal that while CT fosters key cognitive and motor skills, the lack of appropriate materials and teacher training hinders effective implementation. The article highlights the need for continuous teacher training programs and the comprehensive inclusion of CT in early childhood curricula. Furthermore, it identifies a lack of consistent assessment tools that measure the long-term effects of these interventions on child development.